A autoconfrontação e seus usos no campo da linguística aplicada ao estudo do trabalho do professor - Messias, Carla; Perez, Deivis [UNESP] (My University, 2013)
The objective of this study was to present the use of selfconfrontation in applied linguistics (AL) research on teachers’ activities. Selfconfrontation was developed by Faïta (1997), and improved by Clot (2006) within the context of Activity Clinics. It is a device that attempts to capture the multiple discourses around an activity and enable its transformation by workers. Thus, a qualitative research approach was employed and documental analysis of theses, dissertations and papers abstracts produced in Brazil (1987 to 2011), available in the electronic site of CAPES, was performed. The results demonstrated that selfconfrontation is used in a fragmented manner in AL studies that examine teachers’ activities, being primarily used for the collection of data, with little emphasis being placed on the transformation of the labor process.

Este artigo apresenta um estudo sobre o uso da autoconfrontação em pesquisas de Linguística Aplicada (LA) sobre o trabalho docente. A autoconfrontação foi criada por Faïta (1997) e aperfeiçoada por Clot (2006) no contexto da Clínica da Atividade. Trata-se de dispositivo que busca captar os múltiplos discursos em torno de um ofício e favorecer sua transformação pelos trabalhadores. Optamos por abordagem qualitativa de pesquisa e realização da análise documental dos resumos de teses, dissertações e artigos produzidos no Brasil (1987 a 2011) disponíveis no site da CAPES. Os resultados apontam que a autoconfrontação é usada de modo fragmentado nos estudos de LA que examinam o trabalho docente, ao servir prioritariamente para recolha de dados e ao conferir menor ênfase para a transformação do processo laboral.
Selfconfrontation and its uses in the field of linguistics applied to teachers’ activities
Keywords: Research methodology; Teachers’ Activities; Applied Linguistics; Activity Clinics.; Metodologia de pesquisa; Trabalho docente; Linguística aplicada; Clínica da atividade